2012
DOI: 10.1073/pnas.1202691109
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a tetratricopeptide repeat-like domain in the nicastrin subunit of γ-secretase using synthetic antibodies

Abstract: The γ-secretase complex, composed of presenilin, anterior-pharynxdefective 1, nicastrin, and presenilin enhancer 2, catalyzes the intramembranous processing of a wide variety of type I membrane proteins, including amyloid precursor protein (APP) and Notch. Earlier studies have revealed that nicastrin, a type I membrane-anchored glycoprotein, plays a role in γ-secretase assembly and trafficking and has been proposed to bind substrates. To gain more insights regarding nicastrin structure and function, we generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 31 publications
1
48
0
Order By: Relevance
“…To do so, we biotinylated IDE in Escherichia coli, immobilized IDE on streptavidin-coated plates, used it to probe a phage-display library, and identified a synthetic antibody in the form of an antigen-binding fragment (Fab). This crystallization chaperone system has effectively facilitated crystallization of membrane proteins and RNA that are otherwise difficult to crystallize (23)(24)(25). The final synthetic antibody, termed Fab (IDE) , bound human IDE with a K D value of 4 nM, as determined by surface plasmon resonance (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To do so, we biotinylated IDE in Escherichia coli, immobilized IDE on streptavidin-coated plates, used it to probe a phage-display library, and identified a synthetic antibody in the form of an antigen-binding fragment (Fab). This crystallization chaperone system has effectively facilitated crystallization of membrane proteins and RNA that are otherwise difficult to crystallize (23)(24)(25). The final synthetic antibody, termed Fab (IDE) , bound human IDE with a K D value of 4 nM, as determined by surface plasmon resonance (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fab was expressed in E. coli strain 55244 and purified using a HiTrap protein G HP column, as previously described (25). Surface plasmon resonance measurements were carried out at 20°C on a Biacore 3000 by immobilizing His-tagged IDE onto a Ni-NTA chip and then injecting 1.2-100 nM of Fab at a flow rate of 30 μL/min (25,34).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other subunits of the complex, NCT, APH-1, and PEN-2 have been known to play roles in its trafficking and maturation. It has been suggested that NCT may be critical for substrate recognition (14,15), although some evidence suggests that NCT may also have a more indirect role in regulation of the localization and activity of the complex (16). Steady-state accumulation of each component of the complex is coordinately regulated and, in large part, is dependent on the expression of the other members of the complex (17)(18)(19).…”
mentioning
confidence: 99%
“…This extracellular domain has been implicated in the stability of the enzyme as well as substrate binding (63), although the latter has been opposed by results showing that recombinant PS (34) and SPP (64) are able to cleave peptide bonds without any cofactor proteins. However, we and others have shown that antibodies against the Nct extracellular domain are capable of inhibiting ␥-secretase activity by competition with substrates (33,65,66), suggesting the possibility that Nct assists in capturing ␥-substrates on the membrane (Fig. 3).…”
Section: Cofactor Proteins Of the ␥-Secretase Complexmentioning
confidence: 99%